Captain Bush and the White Whale of Mass Destruction: Moby-Dick as a Meditation on America - Frazer Merritt (University of Essex Library Services, 2014)
Since its publication 160 years ago, Herman Melville’s Moby-Dick has had an ever-evolving relationship with the American people, particularly at key moments in history. When first published, the novel encountered total rejection, as the populace could not yet understand its profound message. However, with the advent of World War II and Hitler’s monomaniacal quest against the other –Jews, communists, homosexuals and so on–, the American people saw parallels with Captain Ahab. They also saw themselves as the White Whale, illegitimately attacked. The novel’s symbolism resonated with the collective psyche and its popularity soared. There was also a Moby-Dick revival after 9/11. The American people were again attacked by a man in the thrall of his own projections, Osama bin Laden. Like Ahab, though, President George Bush became obsessed with his own whale, Iraq. Bush wanted to wage war against evil itself –the “axis of Evil”– and projected the nation’s shadow onto Saddam Hussein. Manipulation and lies misled the American people into a disastrous war that arguably crippled the nation, much like Ahab manipulated his crewmates and destroyed the Pequod. Melville’s nightmare about America finally became reality. : Essex Student Journal Volume 6 Issue 2 2014